Protective Effects of Hydrogen-Rich Saline on Experimental Intestinal Volvulus in Rats. Issue 7 (14th July 2022) - Oral, Hayrunnisa; Türkyılmaz, Zafer; Karabulut, Ramazan; Kaya, Cem; Dayanır, Duygu; Karakaya, Cengiz; Sonmez, Kaan
Abstract: Background: Intestinal volvulus can cause morbidity and mortality. Surgical reduction, on the other hand, could result in ischemia-reperfusion (I/R) injury. Hydrogen rich saline solution (HRSS neutralizes free radicals in the body. This study aimed to investigate the effects of HRSS in I/R injury in experimental intestinal volvulus in rats. Methods: Thirty rats were randomly allocated into 5 groups. All procedures were done under general anesthesia and sterile conditions in each animal. Five ml/kg of saline and HRSS were administered intraperitoneally (ip) in Sham (Group 1) and HRSS (Group 2) groups, respectively. Groups 3, 4, and 5 constituted the study groups in which volvulus was created in a 5-cm- long ileal segment 2 cm proximal to the ileocecal valve. After 2 hours the volvuli were reduced and following 2 hours of reperfusion, these segments were removed. In volvulus-I/R group (Group 3) no additional procedure was done. HRSS was administered shortly before reperfusion (reduction of the volvulus) in Treatment I (Group 4) and 1 h before experimental volvulus in Treatment II (Group 5) groups. Blood and intestinal tissue samples were obtained from all rats at the 4th hour. Both tissue and blood total oxidant (TOS) and antioxidant status (TAS) levels were determined and tissue histomorphologies were studied. Oxidative stress indices (TOS ÷ TAS) (OSI) were calculated. Results: Tissue TOS and OSI levels and histomorphological injury scores were statistically lower in treatment groups than I/R group, whereas blood TOS and OSI levels were similar between the groups. Conclusions: This study provides biochemical and histomorphological evidence that HRSS prevents intestinal damage in I/R injury caused by volvulus.